Ray-tracing analysis from hybridized utilizing sunlight and supplementary horticulture illumination - Tay, Kong Yew (Nanyang Technological University, 2024)
Building a vertical farm can be costly, and high energy consumption can deter farmers from implementing the setup on their farms. With limited space and rising costs in Singapore, the demand for cheaper farming methods has been on the rise. To combat high energy use, the Agri-PV concept uses solar panels to convert solar energy into electrical energy. The objective of this research will be to identify the effects of shading on plants and to find out if raytracing can be used as a viable method to predict plant yield. The lighting planning software ReluxDesktop will be used to perform raytracing simulations. Concurrently, experiments will also be conducted on an actual setup where data obtained will be used to compare results. The plants will be harvested after 30 days and will be weighed. Results from the raytracing simulation show that the light level can be too high for the plants if no shading is used. The highest recorded lux value usually occurs at 1 pm Singapore time, when the solar panels will not provide much shade. The harvest data shows low yield and mass without shade but improves when shade is applied. Overall, raytracing can be used to predict the outcome by calculating the lux received. Implementing shade has shown improvements in the yield.